ANALISIS PRINSIP MOTION GRAPHIC PADA VIDEO THE GENIUS OF MARIE CURIE - Adelina Pakpahan (Wimba : Jurnal Komunikasi Visual, 2022)
Motion graphic is a combination of images, animations, graphics, and other 2D or 3D media who had a purpose to deliver messages or informations that can connect with audiences’ emotions. To be able to create a good motion graphic, it’s necessary to understand what principles are needed and the important aspects in the making of the motion graphic itself. The genius of Marie Curie (2017) is a motion graphic video from TED-Ed channel on Youtube platform. This video tells a story about Marie Curie, one of the most brilliant female scientists who contributed a lot especially in the science field because of how genius she is. In this article, we will analyze the principles of motion graphic that are applied to the video The genius of Marie Curie (2017). The method that we will be used in this research is literature study and descriptive analysis. The results of the research will be discussed based on the existing theory in the literature review to obtain answers. keyword: motion graphic, video, animation